Thermal analysis of concrete gravity dam - Bùi Anh Kiệt (Tạp chí Khoa học Đại học Mở Thành phố Hồ Chí Minh - Kỹ thuật và Công nghệ, 2012)
In practice of massive concrete constructions, cracks appear so popularly. Thermal behavior in concrete is the important cause of this problem.Based on this reason, the thermal analysis of concrete is very neccessary to find the reasonable solution to prevent cracking in design massive concrete constructions, especially hydroelectric power because of high hydraulic pressure. This pressure cause cracking which induce aggressive phenomenon.So that, the objectives of this paper are: - To research and install thermal modelling in gravity concrete dam by using Ansys software.- To determinate the temperature by time that generated inside each block.